Patient satisfaction and out-patient services assessment in a tertiary hospital of South Odisha, India - Kshatri, J. S.; Karmee, Nivedita; Patro, Sithun Kumar; Tripathy, R. M. (International Journal of Advances in Medicine, 2017)
Background: The out-patient department of a hospital is for patients who do not require hospitalization but have come for their health needs, either for treatment or for diagnosis. The main objective of the study was to measure the satisfaction levels of the patients attending the OPDs of MKCG medical college. Methods: Data were collected from OPD patients through pre-structured questionnaires in the local languages at the OPD of MKCG Medical College. The data were analysed using SPSS. Results: Out of total 100 patients interviewed, 58 were males and 42 were females. 13% respondents were "highly unsatisfied" with the OPD services where as 65% were "unsatisfied", 15% were "satisfied" and only 7% "highly satisfied". 27% of the participants were from lower socio-economic status (SES), 70% were from middle class and the rest from upper class. 100% of those belonging to upper SES, 80% of middle SES and 70% of lower SES were highly unsatisfied or unsatisfied with OPD services. Most of the patients had come to attend the departments of Medicine (25%), Paediatrics (18%), Surgery (16%) and Obstetrics and Gynaecology (15%). 45% patients were visiting this facility for the first time. 11% of these new patients were Highly satisfied with the services while 31% of repeat patients were either satisfied or highly satisfied. The median waiting time between arrival and consultation was 1 hour. 84% participants had to incur out of pocket expenses. The mean amount spent was Rs. 350. 80% of those who had spent were of the opinion that they had to spend more than what was reasonable. Conclusions: Patient satisfaction was significantly associated with SES, repeat visits, and waiting time between arrival and consultation. Measures to reduce out of pocket expenditure and waiting time may increase satisfaction levels in patients.